Student's Perceptions Of Buzan and Edward's Concept Map Strategy For Teaching Arabic/ آراء الطلاب في استخدام استراتيجية الخريطة عند بوزان وإدوارد المفاهيمية - Penny Respati Yurisa; Nurul Murtadho; Umi Machmudah; Abdur Rosid (Ijaz Arabi Journal of Arabic Learning, 2022)
Indonesian students are weak in critical thinking, as well as the curiosity of researchers about what strategies are suitable for improving speaking skills, this study aims to find a strategy using concept maps with several stages that will train students' skills in reading, vocabulary, write and speak. This study aims to describe the application of the concept map strategy and describe the obstacles faced by students, as well as solutions, as well as describe student perceptions. This study uses a qualitative descriptive approach with case studies, which focus on learning at Malang State Universities and Maulana Malik Ibrahim State Islamic University Malang, Indonesia. Data are collected by observation, interviews and documentation. As for the data analysis method, the researcher used the model according to Miles and Huberman, the data analysis technique consisted of data collection, condensation, data presentation, and drawing conclusions. The results of this study are students' perceptions in implementing the strategy are divided into two, the beginning of application (aspects of mastery of the material, duration of time, habituation of learning and technology) and after application (aspects of vocabulary, compulsion, facilitating learning and psychological). concept map strategy trains students to think critically and speak systematically and learn independently.